Masa dan masyarakat Melayu: peradaban berterusan (Jurnal Bahasa, 2022)
The notion of 'Malay promise' (meaning 'not punctual') persists till today. In the past when absence of instruments for observing time was usually held responsible for unpunctuality, the availability of clocks and watches in present day society does not seem to solve the so-called problem of lack of promptness. Concomitant with this, the existence of malay phrases such as, 'the duration of a hombill s incubation', 'the duration of the ripening of a papaya', and 'the duration of the ripening of the rambai fruit' seems to belie this assumption of unpunctuality. This is because they do indicate a conception of time, which includes consideration of duration and period. The currency of such sayings would suggest that Malay concept of time, as understood in olden times persists despite rapid changes in modern society. In fact the former phrases of time has changed to 'afterasar (early evening) prayer', 'after maghrib (evening) prayer', and dusk in todays life. This observation lends itself to a relevant question. Are Malays so inflexible that changes wrought by modernization and globalisation failing to affect any significant shift in their perception of time? Or, could this so-called rigidity be explained in terms of the built-in leeway, which inevitably accompanies any conception of time, a way of thinking which in turn explains Malay tolerance and politeness. To this end, data form both modern and traditional texts are analyzed from the perspective of pragmatics. The findings would prove whether Malay way of conceiving time is eroded or reinforced and strengthened over time.